Green Portable Folding Home (GPFH) / Nur Nabilah Jamaludin and Asmat Ismail - Jamaludin, Nur Nabilah; Ismail, Asmat (2023)
The background of this research based on Rancangan Malaysia Kedua Belas, Green Technology Master Plan and Sustainable Development Goals 7 and 11. This research examines the residential issues of expensive housing, damage to existing houses due to floods, and housing problems resulting from migration to explores the potential of green development solutions such as solar energy and rainwater harvesting tanks, along with innovative housing options like Tesla Tiny House and Boxabl Casita. The aim is to develop existing expandable container houses and tesla tiny house to become green portable folding homes which can help people to have an affordable sustainable house which is practical for any situation. The research adopts a quantitative methodology, employing document review, design thinking and 3D modelling simulation. The key findings of the study reveal that GPFH presents a viable solution for young families starting their lives, as well as for veterans who intend to utilize their pension funds for home construction. Moreover, individuals residing in flood-prone areas find GPFH practical as they can be easily lifted above floodwaters, preventing damage to the house. GPFH not only provides affordable housing but also promotes sustainable living through the incorporation of green technologies. It is recommended to produce a real product for usability study to test water usage and backup plan for rainwater harvesting. Other than that, implement water filter, measure solar energy and add electricity backup and determine capacity of green portable folding home.